State-Owned Or State-Owed? Evaluating Indonesia'S Divestment Returns From Pt Vale Indonesia Tbk - Daulay, Anggi Anugerah; Qadri, Resi Ariyasa (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2024)
This study endeavors to predict and elucidate the prospective returns on governmental investments in the divestment shares of PT Vale Indonesia Tbk. Financial data were collated through the documentation technique, leveraging annual reports from the company. The financial information was subsequently analyzed employing a quantitative methodology"” specifically, the discounted cash flow model"”to ascertain the intrinsic value of the firm. The findings indicate that the intrinsic value of PT Vale Indonesia Tbk. surpasses its market price on the stock exchange, suggesting that the investment by the Indonesian government is poised to yield capital gains. However, the potential for dividend earnings appears limited due to the company's inconsistent history of dividend distribution. This research contributes to the enhancement of governmental investment strategies in divestment shares and provide valuation recommendations for PT Mineral Industri Indonesia, which has been designated by the Government of Indonesia to acquire shares in PT Vale Indonesia Tbk.